Najczęstsze choroby przeciążeniowe występujące u osób uprawiających balet = The most common disease occurring in the overload of people practicing balet - Michalczak, Magdalena; Bojarczuk, Katarzyna; Smoleń, Agata (Journal of Education, Health and Sport, 2016)
Michalczak Magdalena, Bojarczuk Katarzyna, Smoleń Agata. Najczęstsze choroby przeciążeniowe występujące u osób uprawiających balet = The most common disease occurring in the overload of people practicing balet. Journal of Education, Health and Sport. 2016;6(7):630-639. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60829 http://ojs.ukw.edu.pl/index.php/johs/article/view/3777 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.07.2016. Revised 25.07.2016. Accepted: 28.07.2016. Najczęstsze choroby przeciążeniowe występujące u osób uprawiających balet The most common disease occurring in the overload of people practicing balet Magdalena Michalczak, Katarzyna Bojarczuk, Agata Smoleń Katedra i Zakład Epidemiologii i Metodologii Badań Klinicznych Uniwersytetu Medycznego w Lublinie Słowa kluczowe: choroby przeciążeniowe; balet; urazy sportowe. Key words: disease overload; ballet; sports injuries. Abstrakt Wprowadzenie: Przeciążenia narządu ruchu u osób uprawiających balet niewątpliwie przyczyniają się do powstawania wielu chorób. Popularność medialna sportu, pogoń za rekordami, zwiększanie obciążeń treningowych do granic wytrzymałości organizmu doprowadziły do wzrostu liczby tzw. urazów sportowych. Po latach treningów dochodzi do degeneracji stawów i struktur kostnych, co objawia się bólem oraz ograniczeniami ruchów. Jak wykazują statystyki u zawodowych sportowców dysfunkcja stawów stanowi często problem już po 30-40 roku życia. Przyczyną są nie tyle urazy, co zużycie stawów związane z dużymi obciążeniami podczas treningu i zawodów. Cel pracy: Przedstawienie najczęściej występujących chorób przeciążeniowych narządu ruchu u osób uprawiających balet. Materiał i metody: Metodą badawczą była analiza i krytyka piśmiennictwa. Przedmiotem metody jest literatura medyczna z zakresu ortopedii i rehabilitacji. Stan wiedzy: Przeciążenia narządu ruchu zarówno statyczne jak i dynamiczne są najczęstszą przyczyną dolegliwości bólowych stawów kończyn dolnych. To właśnie powtarzające się przeciążenia doprowadzają do powstawania zmian zwyrodnieniowych oraz przyczyniają się do urazów mechanicznych tkanek miękkich (więzadeł, mięśni, torebki stawowej). Podsumowanie: Najczęstszymi chorobami wywołanymi przeciążeniami narządu ruchu są głównie: uszkodzenia łąkotek kolana, przewlekłe nawrotowe zapalenie torebki maziowej, zapalenie kaletek maziowych, uraz więzadeł pobocznych, uraz więzadeł krzyżowych, jałowa martwica guzowatości piszczeli oraz uszkodzenie ścięgna Achillesa. Abstract Introduction: Overload musculoskeletal patients practicing ballet undoubtedly contribute to the formation of many diseases. Popularity media sport, chasing records, increasing training loads to the limits of the body led to an increase in the number of so-called. sports injuries. After years of training, degeneration of joints and bony structures, resulting in pain and restricted movement. As shown by statistics from professional athletes joint dysfunction is a common problem after 30-40 years of age. The reason is not so much trauma that wear the joints associated with heavy loads during training and competition. Objective: Presentation of the most common diseases of musculoskeletal overload in people practicing ballet. Material and Methods: The research method was the analysis and critique of literature. The subject of the method is the medical literature in the field of orthopedics and rehabilitation. State of the art: Overload musculoskeletal both static and dynamic are the most common cause of pain in the joints of the lower limbs. It was repeated overload lead to the formation of degenerative changes and contribute to the mechanical trauma of soft tissues (ligaments, muscle, joint capsule). Summary: The most common diseases caused by overload the musculoskeletal system are mainly damaged meniscus knee, chronic recurrent inflammation of bursitis, inflammation of the bursae, trauma collateral ligament, cruciate ligament injury, avascular necrosis of the tibial tuberosity and damage to the Achilles tendon.